CLOSANTEL AS A POTENTIAL LIPOPOLYSACCHARIDE BIOSYNTHESIS INHIBITOR IN SHIGELLA SONNEI 4303 - DEUTSCH-NAGY, Laura; URBÁN, Péter; SZEBENI, Hunor; ALBERT, Beáta; KOCSIS, Béla; KILÁR, Ferenc (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Shigella spp. are Gram-negative intracellular pathogenic bacteria belonging to the family Enterobacteriaceae. The pathophysiological impact of the bacteria is highly related to the composition and structural variability of lipopolysaccharides. Serum sensitivity and biofilm forming ability are correlated with the length of these molecules, while bacteria with truncated lipopolysaccharides are more sensitive to hydrophobic antibiotics. Inhibitors of lipopolysaccharide biosynthesis have the potential to develop new antimicrobial agents or antibiotic adjuvants. Bacterial two-component systems enable bacteria to sense and to respond to the changes in different environmental conditions. This study focuses on the inhibition of the rfaD gene encoding the ADP-L-glycero-D-mannoheptose-6-epimerase, which is involved in the lipopolysaccharide biosynthesis. Although there are some inhibitors presumed for bacterial two-component systems like Closantel, their impact on lipopolysaccharide biosynthesis has not been examined previously. The Shigella sonnei 4303 strain was involved in the experiments with known lipopolysaccharide structure. The effect of Closantel on lipopolysaccharide biosynthesis and the limitations of its use are presented.